2005
DOI: 10.1080/00365590410002537
|View full text |Cite
|
Sign up to set email alerts
|

Costs of radical cystectomy

Abstract: Total costs may be very high for a cystectomy with complications. Peri-operative blood loss was the most important factor associated with high total hospital costs for radical cystectomy due to bladder cancer. If the amount of bleeding can be influenced then substantial reductions in the total costs of cystectomy would seem possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…Other studies have also shown a significant association between substantial blood loss and a higher complication rate [18]. However, the level of perioperative bleeding noted in the current study is lower than the average blood loss of 3900 ml described in an earlier report concerning cystectomies performed in Sweden in the 1990s [19].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Other studies have also shown a significant association between substantial blood loss and a higher complication rate [18]. However, the level of perioperative bleeding noted in the current study is lower than the average blood loss of 3900 ml described in an earlier report concerning cystectomies performed in Sweden in the 1990s [19].…”
Section: Discussioncontrasting
confidence: 67%
“…A similar reduction is also noticeable in Sweden when comparing the present results with findings from the 1990s Note that an individual patient could be registered for more than one reoperation and hence give a higher number than the 37 (13%) registered as having undergone reoperation. [19]. Furthermore, in the USA during the abovementioned period, the readmission rates within 30 days of surgery remained stable at 25%, while the use of skilled nursing and intermediate care after discharge increased from 8% to 18% [20].…”
Section: Discussionmentioning
confidence: 88%
“…A study at a single Swedish institution showed that peri-and post-operative complications were associated with costs 2.1 and 3.1 times higher than uncomplicated surgeries [90]. In studies of nationwide samples in the USA, hospital-acquired complications such as septicemia were associated with significantly higher costs and mortality [63,91,92].…”
Section: Economic Evaluationsmentioning
confidence: 98%
“…11 Moreover, blood transfusions are closely related to high total hospital costs in patients undergoing radical cystectomy. 24 Therefore, it is reasonable to decrease the number of intraoperative blood transfusions. Various strategies, such as a combining epidural with general anesthesia, 25 new technical apparatuses for hemostasis, 26,27 autotransfusion using intraoperative cell salvage, 28 and meticulous surgical performance may help reduce blood loss, the need for …”
Section: Discussionmentioning
confidence: 99%